2016
DOI: 10.1002/2016jg003328
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increasing temperatures on methane concentrations and methanogenesis during experimental incubation of sediments from oligotrophic and mesotrophic lakes

Abstract: Global warming is expected to raise temperatures in freshwater lakes, which have been acknowledged to contribute up to 10% of the atmospheric methane concentrations. Increasing temperature enhances methane production and oxidation rates, but few studies have considered the balance between both processes at experimentally higher temperatures within lake sediments. The temperature dependence of methane concentrations, methane production rates, and methanogenic (mcrA) and methanotrophic (pmoA) community size was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 95 publications
8
47
1
Order By: Relevance
“…In addition to changes to thermal structure, warming and thawing of permafrost in the Arctic may allow organic carbon, nutrients, and ions that were previously frozen in sediments to be transported into aquatic systems and become available for microbial utilization (Kokelj et al, 2009;Lougheed et al, 2011;Weyhenmeyer et al, 2011). Experimental laboratory incubation studies have also demonstrated that microbial CH 4 production significantly increases with increased temperature (Duc et al, 2010;Lofton et al, 2013;Fuchs et al, 2016).…”
Section: Introductionmentioning
confidence: 82%
“…In addition to changes to thermal structure, warming and thawing of permafrost in the Arctic may allow organic carbon, nutrients, and ions that were previously frozen in sediments to be transported into aquatic systems and become available for microbial utilization (Kokelj et al, 2009;Lougheed et al, 2011;Weyhenmeyer et al, 2011). Experimental laboratory incubation studies have also demonstrated that microbial CH 4 production significantly increases with increased temperature (Duc et al, 2010;Lofton et al, 2013;Fuchs et al, 2016).…”
Section: Introductionmentioning
confidence: 82%
“…Fundamentally, it can be quite challenging to conduct controlled long‐term experiments in the field, and these experiments may also be subject to some bias. By using laboratory experimentation to study microbial communities under defined conditions, such as increases in temperature (Fuchs et al ., ) or organic matter concentrations (Babbin et al ., ), novel insight can be gained into causal relationships among biogeochemical processes that exist in nature, and how these processes might be expected to change in response to environmental stimuli. Ideally, both controlled laboratory enrichments and careful experiments performed at field sites can function together as complementary approaches to resolve difficult microbial ecology issues.…”
Section: Discussionmentioning
confidence: 99%
“…Both of the latter two effects may have been caused by reconstituting of the sediments. Previous studies have demonstrated the temperature dependence of methane generation and emissions [ Crill and Martens , ; Yvon‐Durocher et al , ], although in some cases the resultant increase in methane oxidation can balance this effect and even reduce sediment methane concentrations [ Duc et al , ; Fuchs et al , ]. The sonar may also underestimate fluxes due to limitations in sensitivity to small bubbles, though those did not contribute significantly to the flux in the tank (Figure ).…”
Section: Discussionmentioning
confidence: 95%